Pengembangan Media Pembelajaran Menggunakan Adobe Flash Materi Balok dan Kubus Kelas VIII SMP Negeri 9 Satap Langowan - Pai, Rijelio Nathanael; Kaunang, Derel F.; Maukar, Marvel G. (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
The use of technology in teaching and learning activities can increase the effectiveness of learning. Learning media is an important aspect used in the teaching and learning process which can be developed using technology such as learning media using Adobe Flash. The aim of this research is to develop the use of Adobe Flash learning media in learning blocks and cubes material for class 8 of SMP Negeri 9 Satap Langowan. and knowing the quality of the material from three aspects, namely validity, practicality and effectiveness. This type of research is Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. According to the Validity aspect, the percentage from media experts is 95.3% with very valid criteria, from material experts 87.3% with very valid criteria, and the percentage from the practical aspect is 96.88% with very practical criteria, and the percentage from the effectiveness aspect is 95. 45% with effective criteria. So it can be concluded that the learning media using Adobe Flash is valid based on expert assessments, interesting based on the results of student response questionnaires, and effective based on student learning outcomes tests.